Understanding Agrarian Reform in Colombia: The Story from a Field Visit during the International Land Grabbing Conference 2024 - Sinaga, Randa Putra Kasea; Saragih, Mujahid Widian (Talenta Publisher, 2024)
During the International Land Grabbing Conference 2024 in Colombia, the authors had the opportunity to visit two sites of agrarian reform struggle in the Department of Cundinamarca, where efforts to curb land grabbing are being implemented: the San JoaquÃn Farm in the municipality of Puerto Salgar, and the Zona Reservo Campesino in the municipality of Venecia. Given the long-standing history of agrarian issues in Colombia and the hopeful political will of the current Colombian president, it is intriguing to discuss the authors' findings from this field visit to understand the achievements in the implementation of agrarian reform in Colombia, as well as the challenges faced in resolving agrarian issues confronted by farmers and rural communities. Based on observations, it is evident that the success of agrarian reform implementation relies on the political will of the government and efforts to involve farmer organizations, as well as addressing policy barriers. A state-centered approach, with the involvement of social actors such as farmer organizations and NGOs, can overcome structural and institutional obstacles. Furthermore, sustainable livelihoods for farmers must be prioritized, considering the cultural and historical context of the farmers and the need for balanced resource management with a subjective approach to agricultural organization, which can facilitate farmer regeneration and the success of agrarian reform in Colombia.